1999
DOI: 10.1021/la981308v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Diffusion Measurements and Coke Distribution in Zeolite Pellets:  A Study by 1H NMR Imaging and 129Xe NMR Spectroscopy

Abstract: Diffusion of benzene in HZSM-5 zeolite in powder or pellet form and of 2,3-dimethylpentane (DMP) in HY zeolite pellets, more or less deactivated by formation of coke during n-heptane cracking, was studied by 1H NMR imaging and 129Xe NMR of adsorbed xenon used as a probe. The shape and the evolution of the signal intensity of the 1D profile, representing the proton distribution along the axis of the cylindrical tube containing the catalyst, make it possible to determine the intracrystalline molecular diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…[12][13][14][15][16] The value of 129 Xe NMR using thermally polarized (i.e., nonoptically pumped) xenon for intracrystalline hydrocarbon diffusion studies at low temperature in heterogeneous catalysts has been demonstrated extensively in the recent past. [17][18][19][20][21] The combustion process within the coil region of the NMR probe head (Figure 1) takes place on and above the surfaces of molecular sieve pellets (i.e., only partially dehydrated Na-X zeolite). Although catalytic activity of this material is not expected, the reaction may still be influenced by the zeolite surface in contact with the flame.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] The value of 129 Xe NMR using thermally polarized (i.e., nonoptically pumped) xenon for intracrystalline hydrocarbon diffusion studies at low temperature in heterogeneous catalysts has been demonstrated extensively in the recent past. [17][18][19][20][21] The combustion process within the coil region of the NMR probe head (Figure 1) takes place on and above the surfaces of molecular sieve pellets (i.e., only partially dehydrated Na-X zeolite). Although catalytic activity of this material is not expected, the reaction may still be influenced by the zeolite surface in contact with the flame.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by imbibing cyclohexane within the catalyst. Microimaging has also been used at the single-pellet level [34] and in small beds of pellets to map coke distribution [35,36]. Therefore, by spatially resolving the T 1 of cyclohexane within the catalyst, the distribution of the hexachloroplatinate dianion is determined.…”
Section: Imaging Individual Catalyst Pelletsmentioning
confidence: 99%
“…More recently, changes in liquid distribution within a catalyst pellet during reaction have been studied [33]. For example, Bonardet et al [35] imaged the 1 H spin density associated with 2,3-dimethylpentane probe molecules adsorbed on pellets of HY zeolites coked to levels of 7.5 and 10% w/w. Figure 3 shows the spatial maps of the liquid phase within the catalyst pellet under catalytic reaction conditions.…”
Section: Imaging Individual Catalyst Pelletsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent measurements of molecular diffusion [4][5][6][7], liquid distribution during reaction [8] and coke distribution [9][10][11] within both single catalyst pellets and arrays of such pellets have been addressed. These studies have used both spatially unresolved and microimaging MR methods.…”
Section: Introductionmentioning
confidence: 99%